2018
DOI: 10.1038/s41388-018-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type p53 upregulates an early onset breast cancer-associated gene GAS7 to suppress metastasis via GAS7–CYFIP1-mediated signaling pathway

Abstract: The early onset breast cancer patients (age ≤ 40) often display higher incidence of axillary lymph node metastasis, and poorer five-year survival than the late-onset patients. To identify the genes and molecules associated with poor prognosis of early onset breast cancer, we examined gene expression profiles from paired breast normal/tumor tissues, and coupled with Gene Ontology and public data base analysis. Our data showed that the expression of GAS7b gene was lower in the early onset breast cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1,003
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(1,006 citation statements)
references
References 42 publications
0
1,003
0
Order By: Relevance
“…Lastly, we will discuss the category "regulation of key signaling pathways and actin cytoskeletal pathways" based on the expression profiles of PCNA, CDK4, cyclin D1, and p21 of THP-1 cells following silencing of miR-362-5p or induction of GAS7. Previous work has revealed that, some events, such as Stat5-, AKT-, Erk-, and CYFIP1mediated signaling pathways can be affected by GAS7 in some particular types of cells [34,35]. Chang et al [34] indicated that p53 upregulate GAS7, thus attenuating breast cancer cells metastasis through regulating CYFIP1 and WAVE2 complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we will discuss the category "regulation of key signaling pathways and actin cytoskeletal pathways" based on the expression profiles of PCNA, CDK4, cyclin D1, and p21 of THP-1 cells following silencing of miR-362-5p or induction of GAS7. Previous work has revealed that, some events, such as Stat5-, AKT-, Erk-, and CYFIP1mediated signaling pathways can be affected by GAS7 in some particular types of cells [34,35]. Chang et al [34] indicated that p53 upregulate GAS7, thus attenuating breast cancer cells metastasis through regulating CYFIP1 and WAVE2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has revealed that, some events, such as Stat5-, AKT-, Erk-, and CYFIP1mediated signaling pathways can be affected by GAS7 in some particular types of cells [34,35]. Chang et al [34] indicated that p53 upregulate GAS7, thus attenuating breast cancer cells metastasis through regulating CYFIP1 and WAVE2 complex. On the contrary, GAS7 has a proproliferative role in pre-B acute lymphoblastic leukemia cells, possibly through regulating Stat5, AKT, and Erk proliferation signals [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…FOXN4 mainly function as transcriptional repressor to suppress P53 expression from mRNA and protein levels. P53, the most famous tumor suppressor, which controls several biological processes such as cell cycle, EMT, cell survival, metastasis and metabolism, [21][22][23] is frequently inactivation in breast cancer and is considered a constant feature of cancer. [24][25][26] In this study, we explored molecular changes associated with loss of p53 in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…GAS7 is expressed primarily in terminally differentiated brain cells and plays a putative role in neuronal development [27]. Recent researches supported that GAS7 involves cancer development and metastasis [28,29]. Moreover, GAS7 was also reported to associate with drug resistance.…”
Section: Discussionmentioning
confidence: 99%